Feruloyl-CoA 6′-Hydroxylase1-Dependent Coumarins Mediate Iron Acquisition from Alkaline Substrates in Arabidopsis. Issue 1 (18th November 2013) - Schmid, Nicole B.; Giehl, Ricardo F.H.; Döll, Stefanie; Mock, Hans-Peter; Strehmel, Nadine; Scheel, Dierk; Kong, Xiaole; Hider, Robert C.; von Wirén, Nicolaus
Abstract : The release of F coumarins is a component of the reduction-based iron acquisition machinery that helps plants to mobilize iron under alkaline conditions . Abstract: Although iron (Fe) is one of the most abundant elements in the earth's crust, its low solubility in soils restricts Fe uptake by plants. Most plant species acquire Fe by acidifying the rhizosphere and reducing ferric to ferrous Fe prior to membrane transport. However, it is unclear how these plants access Fe in the rhizosphere and cope with high soil pH. In a mutant screening, we identified 2-oxoglutarate-dependent dioxygenase Feruloyl-CoA 6′-Hydroxylase1 (F6′H1) to be essential for tolerance of Arabidopsis ( Arabidopsis thaliana ) to high pH-induced Fe deficiency. Under Fe deficiency, F6′H1 is required for the biosynthesis of fluorescent coumarins that are released into the rhizosphere, some of which possess Fe(III)-mobilizing capacity and prevent f6′h1 mutant plants from Fe deficiency-induced chlorosis. Scopoletin was the most prominent coumarin found in Fe-deficient root exudates but failed to mobilize Fe(III), while esculetin, i.e. 6, 7-dihydroxycoumarin, occurred in lower amounts but was effective in Fe(III) mobilization. Our results indicate that Fe-deficient Arabidopsis plants release Fe(III)-chelating coumarins as part of the strategy I-type Fe acquisition machinery.